Human resources development and the planning process in India - Kohli, Uddesh (ed.); Gautam, Vinayshil (ed.) (New Delhi, 1988)
HUMAN RESOURCES DEVELOPMENT received the required emphasis, for the first time, in the Seventh Five Year Plan. HUMAN RESOURCES DEVELOPMENT is the key to development in all sectors of the economy. Specific problems of HUMAN RESOURCES DEVELOPMENT in individual sectors in Rural Development, Industry & Infrastructure and Services in the planning process in India need to be considered while developing necessary strategies and programmes. This Volume comprises of selected and edited papers from presentations at the National Convention on HUMAN RESOURCES AND THE SEVENTH PLAN organised by the Indian Society for Training and Development in collaboration with Planning Commission, Government of India. In the present form, the anthology is beamed at larger concerns of HUMAN RESOURCES DEVELOPMENT and the Planning process in India. The volume should be useful to lay readers and specialists alike.
Keywords: Human resources - India